Long-term use of pitolisant to treat patients with narcolepsy: Harmony III Study. Issue 11 (29th July 2019) - Dauvilliers, Yves; Arnulf, Isabelle; Szakacs, Zoltan; Leu-Semenescu, Smaranda; Lecomte, Isabelle; Scart-Gres, Catherine; Lecomte, Jeanne-Marie; Schwartz, Jean-Charles; ,
Abstract: Study Objectives: To asses the long-term safety and efficacy of pitolisant, an histamine H3-receptor antagonist, on narcolepsy. Methods: This open-label, single-arm, pragmatic study, recruited adult patients with narcolepsy and Epworth Sleepiness Scale (ESS) score ≥12. After a titration period, patients were treated for up to 1 year with oral pitolisant once-a-day at up to 40 mg. Concomitant stimulants and anti-cataplectic agents were allowed. The primary endpoint was safety; secondary endpoints included ESS, cataplexy, and other diary parameters. Results: Patients ( n = 102, 75 with cataplexy) received pitolisant, for the first time in 73 of them. Sixty-eight patients (51 with cataplexy) completed the 12-month treatment. Common treatment-emergent adverse events were headache (11.8% of patients), insomnia (8.8%), weight gain (7.8%), anxiety (6.9%), depressive symptoms (4.9%), and nausea (4.9%). Seven patients had a serious adverse effect, unrelated to pitolisant except for a possibly related miscarriage. One-third of patients stopped pitolisant, mostly (19.6%) for insufficient benefit. ESS score decreased by 4.6 ± 0.6. Two-thirds of patients completing the treatment were responders (ESS ≤ 10 or ESS decrease ≥ 3), and one third had normalized ESS (≤10). Complete and partial cataplexy, hallucinations, sleep paralysis, and sleep attacks were reduced by 76%, 65%, 54%, 63%, and 27%, respectively. Pitolisant as monotherapy (43% of patients) was better tolerated and more efficacious on ESS than on add-on, but efficacy was maintained in this last case. Conclusions: Long-term safety and efficacy of pitolisant on daytime sleepiness, cataplexy, hallucinations, and sleep paralysis is confirmed.